Pengembangan Dan Implementasi Aplikasi Mobile Learning Pada Mata Pelajaran Bahasa Inggris SMA - Ganda Yoga Swara (Universitas Asahan, 2022)
English lessons are not optimal and seem abstract to students. To overcome this problem, an Android-based English learning media is needed. From the search results, all students already have smartphones, so smartphones can also be used for learning media. The purpose of this research is to produce mobile learning to improve students' abilities and understanding of English subjects. The research method used is the research and development method with the ADDIE model, namely a development model with five stages consisting of analysis, design, development, implementation and evaluation. The data collection instrument consisted of student questionnaire sheets, material expert validation and media expert validation sheets. The results of this study indicate a score of 83% from student questionnaires, 80.6% from material expert validators, and 72.6% from media validators. This means that with an average of 78.73% (good enough / quite valid), then this learning media application is feasible to use in learning English.